Hepatic steatosis induced by nicotine plus Coca-Cola™ is prevented by nicotinamide riboside (NR) - Rivera, Juan Carlos; Espinoza-Derout, Jorge; Hasan, Kamrul M.; Molina-Mancio, Jocelyn; Martínez, Jason; Lao, Candice J.; Lee, Martin L.; Lee, Desean L.; Wilson, Julian; Sinha-Hikim, Amiya P.; Friedman, Theodore C. (Frontiers in Endocrinology, 2024)
Introduction Cigarettes containing nicotine (Nic) are a risk factor for the development of cardiovascular and metabolic diseases. We reported that Nic delivered via injections or e-cigarette vapor led to hepatic steatosis in mice fed with a high-fat diet. High-fructose corn syrup (HFCS) is the main sweetener in sugar-sweetened beverages (SSBs) in the US. Increased consumption of SSBs with HFCS is associated with increased risks of non-alcoholic fatty liver disease (NAFLD). Nicotinamide riboside (NR) increases mitochondrial nicotinamide adenine dinucleotide (NAD+) and protects mice against hepatic steatosis. This study evaluated if Nic plus Coca-Cola™ (Coke) with HFCS can cause hepatic steatosis and that can be protected by NR. Methods C57BL/6J mice received twice daily intraperitoneal (IP) injections of Nic or saline and were given Coke (HFCS), or Coke with sugar, and NR supplementation for 10 weeks. Results Our results show that Nic+Coke caused increased caloric intake and induced hepatic steatosis, and the addition of NR prevented these changes. Western blot analysis showed lipogenesis markers were activated (increased cleavage of the sterol regulatory element-binding protein 1 [SREBP1c] and reduction of phospho-Acetyl-CoA Carboxylase [p-ACC]) in the Nic+Coke compared to the Sal+Water group. The hepatic detrimental effects of Nic+Coke were mediated by decreased NAD+ signaling, increased oxidative stress, and mitochondrial damage. NR reduced oxidative stress and prevented mitochondrial damage by restoring protein levels of Sirtuin1 (Sirt1) and peroxisome proliferator-activated receptor coactivator 1-alpha (PGC1) signaling. Conclusion We conclude that Nic+Coke has an additive effect on producing hepatic steatosis, and NR is protective. This study suggests concern for the development of NAFLD in subjects who consume nicotine and drink SSBs with HFCS.